OVERVIEW; HUBUNGAN ANTARA ADVERSE CHILDHOOD EXPERIENCE, REGULASI EMOSI DAN NON-SUICIDAL SELF-INJURY - Usfal, Veronika F.; Manafe, Rizky Pradita; Takalapeta, Theodora (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Adverse Childhood Experiences (ACEs) are traumatic events during childhood that have long-term impacts on mental health, often hindering emotional maturity and triggering maladaptive coping mechanisms such as Non-Suicidal Self-Injury (NSSI). This study aims to analyze the complex relationship between ACEs, emotion regulation, and NSSI, with a particular focus on the role of emotion regulation as a mediator linking traumatic experiences to self-injurious behavior. Using a narrative literature review, this study synthesized data from relevant scientific articles published between 2015 and 2025 through systematic searches of academic databases such as PubMed and ScienceDirect. Key findings demonstrate consistent evidence that exposure to ACEs is strongly correlated with emotion dysregulation, which subsequently significantly increases the risk of self-injurious behavior without suicidal intent. This study confirms that the inability to manage emotions adaptively is a key mechanistic pathway linking childhood trauma to NSSI behavior. It is concluded that psychological interventions focused on strengthening emotion regulation skills are crucial for mitigating the detrimental impact of ACEs and preventing NSSI behaviors in vulnerable individuals, particularly adolescents. ABSTRAK Adverse Childhood Experience (ACE) merupakan peristiwa traumatis masa kanak-kanak yang berdampak jangka panjang pada kesehatan mental, sering kali menghambat kematangan emosional dan memicu mekanisme koping maladaptif seperti Non-Suicidal Self-Injury (NSSI). Penelitian ini bertujuan untuk menganalisis hubungan kompleks antara ACE, regulasi emosi, dan NSSI, dengan fokus khusus pada peran regulasi emosi sebagai variabel mediator yang menghubungkan pengalaman traumatis dengan perilaku melukai diri. Menggunakan metode tinjauan literatur naratif (narrative literature review), penelitian ini menyintesis data dari artikel ilmiah relevan yang diterbitkan antara tahun 2015 hingga 2025 melalui penelusuran sistematis pada basis data akademik seperti PubMed dan ScienceDirect. Temuan utama menunjukkan konsistensi bukti bahwa paparan ACE berkorelasi kuat dengan disregulasi emosi, yang selanjutnya meningkatkan risiko perilaku melukai diri sendiri tanpa intensi bunuh diri secara signifikan. Studi ini menegaskan bahwa ketidakmampuan mengelola emosi secara adaptif menjadi jalur mekanistik utama yang menghubungkan trauma masa kecil dengan perilaku NSSI. Disimpulkan bahwa intervensi psikologis yang berfokus pada penguatan keterampilan regulasi emosi sangat krusial untuk memitigasi dampak buruk ACE dan mencegah perilaku NSSI pada individu yang rentan, khususnya populasi remaja.